2014
DOI: 10.1111/1756-185x.12335
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid factor in idiotypic regulation of autoimmunity

Abstract: RF detected by agglutination of tanned IgG-loaded erythrocytes is involved in negative idiotypic regulation of lymphocytes specific to autoimmunity-inducing antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Antigen‐antibody complexes can also bind to Fc receptors on the surfaces of B cells, which leads to their antigen‐specific inactivation. According to the Jerne's theory, the immune system functions as a network in which production of certain idiotypic antibodies stimulates release of anti‐idiotypic immunoglobulins, which limit amounts of circulating antibodies after the pathogen has been removed from the organism and they are no longer needed . It has recently been found that B cells may also contribute to immune regulation by releasing antibody‐free light chains.…”
mentioning
confidence: 99%
“…Antigen‐antibody complexes can also bind to Fc receptors on the surfaces of B cells, which leads to their antigen‐specific inactivation. According to the Jerne's theory, the immune system functions as a network in which production of certain idiotypic antibodies stimulates release of anti‐idiotypic immunoglobulins, which limit amounts of circulating antibodies after the pathogen has been removed from the organism and they are no longer needed . It has recently been found that B cells may also contribute to immune regulation by releasing antibody‐free light chains.…”
mentioning
confidence: 99%
“…It is possible that RFs arise in some way in response to the presence of immune complexes that are ACPA‐based, but the well‐known differences between RFs in RA and ‘physiological’ RFs that are often seen after immunization or infections and thought to contribute to immune complex clearance, make such a simple relationship an unlikely explanation. The current study by Bedulova et al . shows how antibodies that show RF activity can be so heterogeneous and reminds us that we will probably have to think well outside the box if we ever are going to be able to grasp the relationship between the two autoantibody systems in RA and have a better idea of perpetuation and potential initiation mechanisms of the autoimmune response in RA.…”
mentioning
confidence: 70%
“…In contrast, Beduleva et al . present a very different study showing how particular subspecies of RFs can play a protective role in animal models of autoimmunity, including collagen‐induced arthritis (CIA).…”
mentioning
confidence: 99%
“…In the context of an infection and inflammation that could induce epitope spreading, molecular mimicry, or cryptic antigens exposure, autoimmune diseases might occur, resulting from a defect of immune response and lack of connection to the network (11). The observation of earlier kinetics of anti-idiotypic response to auto-antigen, before auto-antibody response, also suggests a role of rheumatoid factors recognizing idiotypes of antibodies, in regulation of auto-immunity (12). …”
mentioning
confidence: 99%
“…Likewise, T lymphocytes positively selected on thymic medulla epithelial cells, presenting tissue specific antigens, form a ‘core’ in the global T lymphocyte network, with a repertoire biased to self-cognition and behave as natural regulatory T cells involved in dominant and tissue specific tolerance (14), while presentation of B cell idiotopes is required for full tolerance (15). Immunization conditions and antigen doses are expected to lead to immune, tolerant, or hyper-reactivity conditions (12). Yet, in vivo perturbation and shrinking of the network through aging or transient depletion of dividing lymphocytes affect repertoire composition (16), tolerance (17), and memory maintenance leading to immunological amnesia (18).…”
mentioning
confidence: 99%